Fabrication and assessment of ethosomes for effective transdermal delivery of loxoprofen - Sarah Abd Alhur; Hasanain Mahmood (Iranian Journal of Basic Medical Sciences)
Objective(s): To formulate and evaluate ethosomes for the transdermal delivery of loxoprofen, a potent non-steroidal anti-inflammatory drug (NSAID).Materials and Methods: Fifteen ethosomal formulations were created via thin-film hydration and probe sonication techniques, with variations in the amounts of egg yolk lecithin, ethanol, cholesterol (CHOL), Tween 80 (TW80), and propylene glycol (PG). The formulations were assessed for their particle size (PS), zeta potential (ZP), polydispersity index (PDI), pH, and entrapment efficiency (EE). Field scanning electron microscopy (FSEM) was utilized to evaluate their morphology. The in vitro drug release and ex vivo permeability of the ethosomal formulations were evaluated against those in a hydroethanolic drug solution.Results: The formulation labeled F14, comprising 1% loxoprofen, 1% egg yolk lecithin, 30% ethanol, 5% propylene glycol, and phosphate-buffered saline (PBS) up to 25 ml, was recognized as an optimized ethosomal formulation. These ethosomes demonstrated an average size of 164.2±19 nm, a PDI of 0.280±0.028, a ZP of +45.1±4.5 mV, and an EE of 96.8±0.43%. In vitro and ex vivo tests demonstrated that the ethosomal formulation (F14) showed superior drug release and penetration rates compared to a conventional hydroalcoholic solution. The differential scanning calorimetry (DSC) study showed that loxoprofen was completely trapped within ethosomes. On the other hand, the Fourier transform infrared (FTIR) study confirmed that the drug and the additives did not interact.Conclusion: The current study revealed that loxoprofen can be effectively delivered transdermally via the ethosomal system.